1998
DOI: 10.1161/01.res.82.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Restenosis

Abstract: —Intensive work over the past decade has been directed to the study of vascular gene transfer as an approach to the unresolved problem of restenosis. This effort has resulted in a significant foundation of knowledge relative to the activities of potentially therapeutic gene products as well as the capabilities and limitations of vector systems and mechanical delivery modalities available for effecting the vascular expression of these gene products. In several instances, significant progress has been made by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 152 publications
1
24
0
2
Order By: Relevance
“…As in the case of most previous studies concerning the effects of in vivo gene transfer with adenovirus vector or HVJ/liposome on arterial hyperplasia, 6 in this work, the duration of isolation of the arterial segment for gene transfer was longer than that accepted in the clinical situation. Therefore, the development of more effective gene transfer techniques is essential for clinical application.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…As in the case of most previous studies concerning the effects of in vivo gene transfer with adenovirus vector or HVJ/liposome on arterial hyperplasia, 6 in this work, the duration of isolation of the arterial segment for gene transfer was longer than that accepted in the clinical situation. Therefore, the development of more effective gene transfer techniques is essential for clinical application.…”
Section: Discussionmentioning
confidence: 48%
“…[1][2][3] Accumulating evidence indicates that intimal thickening by balloon injury is regulated by the complex interaction among a variety of growth-regulatory molecules, such as growth factors, vasoactive peptides, inflammatory cytokines or chemokines, etc, and these molecules are therefore regarded as the useful target for treatment of vascular thickening. 4,5 On the other hand, as reviewed, [6][7][8] recent experimental evidence supports the fact that critical intracellular signaling molecules common to the induction and action of these growth-regulatory molecules, such as cdc2 kinase, proliferating-cell nuclear antigen, retinoblastoma protein RB, cyclin kinase inhibitor protein p21 or ras gene, etc, are useful targets for prevention of vascular hyperplasia, and targeting these intracellular signaling molecules is pro-…”
Section: Introductionmentioning
confidence: 97%
“…2,3 Animal studies have demonstrated that local delivery of recombinant viral vectors encoding genes which modulate VSMC and/or endothelial cell (EC) behaviour can reduce the neointimal response to experimental angioplasty. 4,5 There are increasing concerns, however, over the safety, practicality and public acceptability of such viral vectors for clinical use, 6 particularly in the context of non-life-threatening conditions such as angioplasty restenosis. 7 As a result, there is renewed interest in the development of nonviral transfection techniques that circumvent these issues.…”
mentioning
confidence: 99%
“…1 Although relatively safe, nonviral gene delivery, including lipofection, is currently at least 10-fold less efficient. 1 Ultrasound exposure (USE) has been shown to permeabilize plasma membranes and reduce the thickness of the unstirred layer at the cell surface, 2,3 which should encourage DNA entry into cells. Furthermore, many lipofection reagents contain dioleoylphosphatidylethanolamine (DOPE), which encourages DNA "breakout" from endosomes through a physicochemical transition that is known to be accelerated by USE.…”
mentioning
confidence: 99%
“…An alternative strategy is single-dose local administration of agents that can modify the vascular response to injury, including local gene therapy. 1 Viral vectors achieve the highest efficiency, but substantial concerns remain over their clinical safety and long-term efficacy. 1 Although relatively safe, nonviral gene delivery, including lipofection, is currently at least 10-fold less efficient.…”
mentioning
confidence: 99%